Characterization of cadmium‐resistant rhizobacteria and their promotion effects on Brassica napus growth and cadmium uptake. (25th April 2019) - Li, Xingjie; Yan, Zhenning; Gu, Daguo; Li, Dongbo; Tao, Yu; Zhang, Daofeng; Su, Liantai; Ao, Yansong
Abstract: Excessive cadmium (Cd) accumulation in soil can adversely affect plants, animals, microbes, and humans; therefore, novel and uncharacterized Cd‐resistant plant‐growth‐promoting rhizobacteria (PGPR) are required to address this issue. In the paper, 13 bacteria were screened, their partial 16S rRNA sequences determined, and the isolates, respectively, clustered into Curtobacterium (7), Chryseobacterium (4), Cupriavidus (1), and Sphingomonas (1). Evaluation of PGP traits, including indole‐3‐acetic acid (IAA) production, 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase activity, siderophore secretion, and cyanhydric acid production, identified Cupriavidus necator GX_5, Sphingomonas sp. GX_15, and Curtobacterium sp. GX_31 as promising candidates for PGPR based on high IAA or ACC deaminase production. Additionally, root‐elongation assays indicated that inoculating GX_5, _15, or _31 increased Brassica napus root length both in the presence and absence of Cd by 19.75–29.96% and 19.15–31.69%, respectively. Pot experiments indicated that inoculating B. napus with GX_5, _15, and _31 significantly increased the dry weight of above‐ground tissues and root biomass by 40.97–85.55% and 18.99–103.13%, respectively. Moreover, these isolates significantly increased Cd uptake in the aerial parts and root tissue of B. napus by 7.38–11.98% and 48.09–79.73%, respectively. These results identified GX_5, _15, or _31 as excellent promoters of metal remediation by using microorganism‐associated phytoremediation.